Thermal analysis of bamboo fibre and its composites - Shah, Ain Umaira Md; Sultan, Mohamed Thariq Hameed; Cardona, Francisco; Jawaid, Mohamad; Talib, Abd Rahim Abu; Yidris, Noorfaizal (North Carolina State University, 2017)
Thermogravimetric analysis and differential scanning calorimetry were used to study the thermal degradation and thermal stability of bamboo powder and its composites (EP-BFC) in a nitrogen atmosphere. The thermal stability of EP-BFC decreased as the bamboo filler-loading increased. Compared with epoxy, bamboo powder had a lower thermal stability, which reduced the thermal stability for the higher filler-loading composites. The addition of glass fibre to the EP-BFC improved the thermal stability of the new hybrid composites. Both the hybrid and non-hybrid composites exhibited similar thermal-induced degradation profiles that had only one mass loss step. However, a noticeable difference between the percentage value of the degradation between both the hybrid and non-hybrid composites showed that the EP/G-BFC hybrids were more thermally stable than the non-hybrid EP-BFC. Different materials experienced different activities, which were clearly shown from the DSC analysis. Bamboo fibre and non-fully cured epoxy exhibit exothermic peaks, while fully cured epoxy exhibits an endothermic peak.